2017
DOI: 10.1248/cpb.c16-00568
|View full text |Cite
|
Sign up to set email alerts
|

Concise, Protecting-Group-Free Synthesis of (+)-Nemonapride <i>via</i> Eu(OTf)<sub>3</sub>-Catalyzed Aminolysis of 3,4-Epoxy Alcohol

Abstract: A concise, protecting-group-free synthesis of the antipsychotic agent ( )-nemonapride has been achieved featuring a europium(III) trifluoromethanesulfonate (Eu(OTf) 3 )-catalyzed C4 selective aminolysis of a 3,4-epoxy alcohol by benzylamine and an expedient use of the resulting 4-benzylamino-1,3-diol product for constructing the pyrrolidine skeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Eu(OTf) 3 catalytically introduces not only alcohols and thiols but also aryl and aliphatic amines to C3 positions of 2,3‐epoxy alcohols with high regioselectivity, and it exhibits high regioselectivity even for C4‐selective alcoholysis of 3,4‐epoxy alcohols [7] . The catalytic Eu(OTf) 3 activated a 3,4‐epoxy alcohol even in the presence of an aliphatic amine nucleophile to induce aminolysis in high yield [8] . The use of this reaction was demonstrated by the synthesis of a pyrrolidine‐derived bioactive compound via the construction of 3‐hydroxy‐2‐alkyl‐pyrrolidine, which is a pivotal scaffold contained in various alkaloids and bioactive agents [9–11] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eu(OTf) 3 catalytically introduces not only alcohols and thiols but also aryl and aliphatic amines to C3 positions of 2,3‐epoxy alcohols with high regioselectivity, and it exhibits high regioselectivity even for C4‐selective alcoholysis of 3,4‐epoxy alcohols [7] . The catalytic Eu(OTf) 3 activated a 3,4‐epoxy alcohol even in the presence of an aliphatic amine nucleophile to induce aminolysis in high yield [8] . The use of this reaction was demonstrated by the synthesis of a pyrrolidine‐derived bioactive compound via the construction of 3‐hydroxy‐2‐alkyl‐pyrrolidine, which is a pivotal scaffold contained in various alkaloids and bioactive agents [9–11] .…”
Section: Methodsmentioning
confidence: 99%
“…[7] The catalytic Eu(OTf) 3 activated a3 ,4-epoxy alcohol even in the presence of an aliphatic amine nucleophile to induce aminolysis in high yield. [8] The use of this reaction was demonstrated by the synthesis of ap yrrolidine-derived bioactive compound via the construction of 3-hydroxy-2-alkyl-pyrrolidine, which is ap ivotal scaffold contained in various alkaloids and bioactive agents. [9][10][11] Unfortunately,t he net yield of the 3-hydroxy-2-alkylpyrrolidine wasm oderate owingt ot he modestr egioselectivity of the Eu(OTf) 3 -catalyzed aminolysis of the 3,4-epoxy alcohol, indicatingt here is room for further improvement.…”
mentioning
confidence: 99%
“…Thus, we have demonstrated that a catalytic amount of europium (III) trifluoromethanesulfonate (Eu(OTf) 3 ) enables the introduction of alcohols and thiols, as well as aryl and aliphatic amines, onto the C3 position of 2,3-epoxy alcohols with high regioselectivity ( Scheme 1A ) ( Uesugi et al, 2014 ). Eu(OTf) 3 also efficiently catalyzed the C4-selective aminolysis of a 3,4-epoxy alcohol, the synthetic use of which was demonstrated by the efficient synthesis of the antipsychotic agent (+)-nemonapride ( Uesugi et al, 2017 ). Furthermore, the lanthanum (III) trifluoromethanesulfonate (La(OTf) 3 ) catalyst induced anti-Baldwin 5- endo - tet cyclization of trans -3,4-epoxy amines via C4-selective intramolecular epoxide aminolysis to give 3-hydroxypyrrolidines in high yields ( Scheme 1B ) ( Kuriyama et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Therefore, great efforts have been made by several synthetic chemists to develop a variety of synthetic methods for amino alcohols. [5][6][7][8][9] In sharp contrast, the choice of protecting group for the amino alcohols, particularly in terms of simultaneous protecting groups for 1,2-and 1,3-amino alcohols, is limited to two types only [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] (Chart 1). The most frequently used type is isopropylidene N-O acetal (acetonide), the introductions and removals of which are generally performed under acidic conditions [12][13][14][15] (Chart 1a).…”
Section: Introductionmentioning
confidence: 99%